Seasonal activity patterns of Ixodes scapularis and Ixodes pacificus in the United States - Lars Eisen (Ticks and Tick-Borne Diseases)
Knowledge of seasonal activity patterns of human-biting life stages of tick species serving as vectors of human disease agents provides basic information on when during the year humans are most at risk for tick bites and tick-borne diseases. Although there is a wealth of published information on seasonal activity patterns of Ixodes scapularis and Ixodes pacificus in the United States, a critical review of the literature for these important tick vectors is lacking. The aims of this paper were to: (i) review what is known about the seasonal activity patterns of I. scapularis and I. pacificus in different parts of their geographic ranges in the US, (ii) provide a synthesis of the main findings, and (iii) outline key knowledge gaps and methodological pitfalls that limit our understanding of variability in seasonal activity patterns. Based on ticks collected while questing or from wild animals, the seasonal activity patterns were found to be similar for I. pacificus in the Far West and I. scapularis in the Southeast, with synchronous activity of larvae and nymphs, peaking in spring (April to June) in the Far West and from spring to early summer (April to July) in the Southeast, and continuous activity of adults from fall through winter and spring with peak activity from fall through winter (November/December to March). In the colder climates of the Upper Midwest and Northeast, I. scapularis adults have a bimodal seasonal pattern, with activity peaks in fall (October to November) and spring (April to May). The seasonal activity patterns for immatures differ between the Upper Midwest, synchronous for larvae and nymphs with peak activity in spring and summer (May to August), and the Northeast, where the peak activity of nymphs in spring and early summer (May to July) precedes that of larvae in summer (July to September). Seasonality of human tick encounters also is influenced by changes over the year in the level of outdoor activities in tick habitat. Studies on the seasonality of ticks infesting humans have primarily focused on the coastal Northeast and the Pacific Coast states, with fewer studies in the Southeast, inland parts of the Northeast, and the Upper Midwest. Discrepancies between seasonal patterns for peak tick questing activity and peak human infestation appear to occur primarily for the adult stages of I. scapularis and I. pacificus. Study design and data presentation limitations of the published literature are discussed. Scarcity of data for seasonal activity patterns of I. pacificus outside of California and for I. scapularis from parts of the Southeast, Northeast, and Upper Midwest is a key knowledge gap. In addition to informing the public of when during the year the risk for tick bites is greatest, high-quality studies describing current seasonal activity patterns also will generate the data needed for robust model-based projections of future climate-driven change in the seasonal activity patterns and provide the baseline needed to empirically determine in the future if the projections were accurate.